2005
DOI: 10.2139/ssrn.676365
|View full text |Cite
|
Sign up to set email alerts
|

Managerial Behavior and Cost/Profit Efficiency in the Banking Sectors of Central and Eastern European Countries

Abstract: The Working Paper series of the Oesterreichische Nationalbank is designed to disseminate and to provide a platform for discussion of either work of the staff of the OeNB economists or outside contributors on topics which are of special interest to the OeNB. To ensure the high quality of their content, the contributions are subjected to an international refereeing process. The opinions are strictly those of the authors and do in no way commit the OeNB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 31 publications
3
40
0
1
Order By: Relevance
“…The DEA compares each banking sector/bank/branch in the sample with the best practice in the sample, whereby it distinguishes between the efficient 3 Gavurová (2011Gavurová ( , 2012; Šoltés -Gavurová (2013). 4 Rossi et al (2005); Karim et al (2010), who used them to measure efficiency in the European and Malaysian banking sectors. Hartman -Storbeck (1996); Resti (1996); Zago -Dongili (2006); Dai (2010);Cinar (2011);Tabak et al (2011).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DEA compares each banking sector/bank/branch in the sample with the best practice in the sample, whereby it distinguishes between the efficient 3 Gavurová (2011Gavurová ( , 2012; Šoltés -Gavurová (2013). 4 Rossi et al (2005); Karim et al (2010), who used them to measure efficiency in the European and Malaysian banking sectors. Hartman -Storbeck (1996); Resti (1996); Zago -Dongili (2006); Dai (2010);Cinar (2011);Tabak et al (2011).…”
Section: Methodsmentioning
confidence: 99%
“…NPLs are one of the major causes of economic stagnation problems and can lead to efficiency problems of banks and the banking sector. According to Berger -DeYoung (1997), Williams (2004) and Rossi et al (2005), we approach the matter in a direct way by linking managerial behaviour with the bank's efficiency. In this paper, we used regression analysis to examine how major structural characteristics of banks affect the efficiency of banks' lending behaviour.…”
Section: Acta Oeconomica 65 (2015)mentioning
confidence: 99%
“…Studies based upon economies of scale theory argued that size has a positive effect on performance by inducing economies of scale, reflected by the fact that large firms take the advantage of economies of scale in reducing the costs of operations (Bashir, 1999;Said, 2012). Rossi et al (2005) found that larger banks have better performance and better control on the cost side and are more capable of exploiting economies of scale. Muritala (2012) found that firm size is positively related to a firm's performance.…”
Section: Firm Size and Performancementioning
confidence: 99%
“…Yudistira, 2004;Hassan, 2005;Rossi, Schwaiger & Winkler, 2005;Delis & Papanikolaou, 2009;Srairi, 2010;Siddiqui & Shoaib, 2011). As a general rule, larger firms tend to have higher level of efficiency.…”
Section: Bank Sizementioning
confidence: 99%
“…There will be numerous effects to different types of banks. Berger, Hunter & Timme (1993) and also Miller & Noulas (1996) reviewed that wider penetration of market and increase in profit at less cost by large banks, hence better efficiency; while Rossi et al (2005) added another reason that larger banks would have better efficiency to control its cost better. On the other side, the effect of size could be negative for banks that are extremely large due to bureaucracy (Nigmonov, 2010).…”
Section: Bank Sizementioning
confidence: 99%